Knowledge and awareness among smallholders towards practices management to control basal stem rot disease in Bera , Pahang / Mohammad Shahruddin Sulaiman - Sulaiman, Mohammad Shahruddin (Faculty of Plantation and Agrotechnology, 2016)
Basal Stem Rot disease (BSR) caused by fungi of Ganoderma spp. is the major diseases faced by the oil palm industry in Malaysia and Indonesia. Oil palm smallholders as a part of sustainable development of the oil palm industry faced many problems in dealing with this diseases. Knowledge and awareness of smallholders towards this devastating disease should lead them to implement treatments and practices to controlling the diseases from being severe infection. This study was conducted to measure the level of knowledge and awareness of smallholders towards the practices management in order to controlling BSR disease. Random sampling method was applied in the survey to collect the data and 248 respondents were participated in this study in Bera Pahang. Based on the result, many of them recognize about BSR diseases but did nothing of practices management in their fields. However, higher awareness lead farmer's to implement the practices management in their fields thus prevent the disease become more severe.